New seismic design method to improve collapse performance of steel ordinary moment frames. (1st June 2022) - Kim, Taeo; Han, Sang Whan
Abstract: Steel ordinary moment frames (OMFs) have been widely used as a seismic force resisting system in low to moderate seismic regions. In this study, the seismic collapse performance of steel OMFs was evaluated. For this purpose, 9-, 12-, 15-, and 18-story steel OMFs were designed in compliance with ASCE 7 (ASCE, 2017) and its reference standards. To improve the collapse performance of the OMFs, a new design method was proposed with a limiting value of column moment strength ratio. Unlike OMFs designed with ASCE 7 and its reference standards, all OMFs designed with the proposed design method satisfied the target collapse probabilities specified in ASCE 7. To investigate the effectiveness of the proposed design method, seismic loss estimation was also performed. The expected annual losses of OMFs were reduced more than 20% when the OMFs were designed with the proposed design method. Highlights: The seismic collapse performance of steel OMFs were evaluated with collapse probabilities. A new seismic design method with column moment strength ratios was proposed to improve the seismic performance of steel OMFs. The seismic loss estimation was conducted to validate the effectiveness of the proposed method.